A method for synthesizing ultrathin MWW zeolite nanosheets using a small molecule template

By using small molecule template agents and double-headed quaternary ammonium template agents with certain flexibility, the curved hydrophobic carbon chains were constructed, and ultra-thin MWW zeolite nanosheets were successfully synthesized, which solved the use of expensive surfactants and complex post-treatment in the prior art. The process problems achieve efficient and simplified preparation process and good product performance.

CN116199232BActive Publication Date: 2025-02-18ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310018606.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-06
Publication Date
2025-02-18
Estimated Expiration
2043-01-06

AI Technical Summary

Technical Problem

The synthesis of ultrathin MWW zeolite nanosheets in the prior art requires the use of expensive surfactants and complex post-treatment processes, resulting in amorphization of samples, complex operation and expensive.

Method used

Using small molecule template agents, the curved hydrophobic carbon chains are constructed on the surface of the MWW layer plate, and ultra-thin MWW zeolite nanosheets are synthesized using a double-headed quaternary ammonium salt template agent with a certain flexibility, avoiding the use of surfactants.

Benefits of technology

The high-efficiency synthesis of ultra-thin MWW zeolite nanosheets has been achieved, good crystallinity and purity are maintained, and the preparation process is simplified, avoiding the use of expensive surfactants. The product has a large specific surface area and a wide range of silicon-aluminum specific synthesis .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116199232B_ABST
    Figure CN116199232B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing molecular sieves, and aims to provide a method for synthesizing ultrathin MWW zeolite nanosheets using a small molecule template agent. The method comprises: adding silica sol, sodium aluminate, sodium hydroxide, a template agent and deionized water into a beaker, stirring overnight to obtain a mixture gel; performing a crystallization reaction, and obtaining MWW zeolite nanosheets after the product is filtered, washed and dried; the template agent is a single small molecule template agent. The product prepared by the present invention not only maintains good crystallinity and purity, but also can achieve controllable thickness of MWW zeolite nanosheets by adjusting the silicon-aluminum ratio of the feed. The product also has a large specific surface area and a wide synthesis range of silicon-aluminum ratio. The preparation method does not use expensive surfactants for stripping or auxiliary one-step synthesis, thereby avoiding the disadvantages of sample amorphization, complex operation and high price caused by the post-treatment process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to a method for preparing a molecular sieve, and in particular relates to a method for synthesizing ultra-thin MWW zeolite nanosheets. Background Art

[0002] Zeolites, especially silica-alumina zeolites, have been widely used in petrochemical, environmental catalysis and other fields since their discovery. Although the micropores of zeolites have excellent selectivity in the catalytic process, their relatively small pores will also seriously affect the mass transfer and diffusion of reactants and products, leading to rapid carbon deposition and initiation of side reactions. Effective methods to solve the above problems include reducing diffusion limitations by shortening the length of the mass transfer path. Zeolite nanosheets have attracted widespread attention because they can greatly shorten the length of the mass transfer path. For example, MFI and MEL zeolite nanosheets have been extensively studied and synthesized due to their important application value in catalysis. In recent years, many zeolite nanosheets with different topological structures have also been synthesized one after another.

[0003] The discovery of layered zeolites has triggered a wave of research on increasing the exposure of zeolite active sites. A large number of layered zeolites with high specific surface area, large number of active site exposure and high performance have been synthesized by post-treatment of layered zeolites by swelling pillaring, peeling and other methods. For example, ITQ-2, ITQ-6, ITQ-18, MCM-36, etc. are obtained by post-treatment of MCM-22(P), PREFER, NU-6 and MCM-22(P), respectively. MCM-22 (MWW topological structure) has attracted widespread attention due to its unique crystal structure. The MWW layer is 2.5nm thick and presents a hexagonal cup array morphology, in which the two ends of the cup are 12-membered rings and contain a 10-membered ring channel running through the center of the layer. Since the 12-membered ring cup contains a large number of T sites, the thinner the MWW zeolite, the higher the exposure of the 12-membered ring, so the demand for ultra-thin MWW zeolites is increasing day by day.

[0004] Although MWW zeolites such as UZM-8, MCM-56, EMM-10, and ITQ-30 can be synthesized in one step, their low mesoporous specific surface area means that these molecular sieves have not yet achieved a high degree of separation of MWW layers compared to ITQ-2. Román-Leshkov et al. designed a template named Ada-i-16 to synthesize a MWW molecular sieve with a thickness of 2.5nm (single unit cell thickness), namely MIT-1. Corma et al. further developed the method of preparing nanosheet zeolites with surfactants, and proposed a strategy of using traditional templates to guide the generation of zeolite structures and surfactants to synthesize nanosheet zeolites. DS-ITQ-2 with a thickness of 1-2 layers (content of about 70%) was synthesized. Rimer used HMI and commercial surfactant hexadecyltrimethylammonium bromide (CTAB) to synthesize MWW with a thickness of 1-2 layers (content up to 85%). Yang et al. used HMI and dicyclohexylamine as dual templates to synthesize SCM-1 and SCM-6 zeolites with partial and complete separation of MWW layers.

[0005] Although great progress has been made in the one-step synthesis of ultrathin MWW nanosheet zeolites, it still remains at the stage of using surfactant-assisted synthesis. This means that the synthesis of ultrathin MWW nanosheet zeolites still requires the use of expensive surfactants for exfoliation or one-step synthesis, as well as the disadvantages of sample amorphization, complex operation and high price caused by the post-treatment process. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a method for synthesizing ultra-thin MWW zeolite nanosheets using a small molecule template agent.

[0007] To solve the technical problem, the solution of the present invention is:

[0008] A method for synthesizing ultrathin MWW zeolite nanosheets using a small molecule template agent is provided, characterized in that it comprises the following steps:

[0009] (1) Add silica sol (Ludox), sodium aluminate (NaAlO2), sodium hydroxide (NaOH), template (OSDA) and deionized water (H2O) into a beaker and stir overnight to obtain a mixture gel;

[0010] (2) transferring the mixed gel into a reaction kettle and placing it in an oven for crystallization reaction; the reaction product is filtered, washed and dried to obtain MWW zeolite nanosheets;

[0011] In the above steps, the amount of each reaction raw material added is controlled so that the molar ratio of the components contained in the gel before being loaded into the reactor is converted to: 1.0SiO2: 0.016-0.056Al2O3: 0.05-0.15Na2O: 0.4-0.8Template: 40-80H2O;

[0012] The template agent is N,N-diethyl-N,N,N,N-tetramethyl-1,4-diammonium hydroxide butylene (EtMe2(CH2)4Me2Et) or N,N-diethyl-N,N,N,N-tetramethyl-1,5-diammonium hydroxide pentane (EtMe2(CH2)5Me2Et).

[0013] As a preferred embodiment of the present invention, when the template is used in step (1), it is added in the form of an aqueous template solution and mixed.

[0014] As a preferred embodiment of the present invention, the mass percentage of the silica sol in step (1) is 40 wt.%.

[0015] As a preferred embodiment of the present invention, step (1) further comprises adding MWW zeolite seeds to the mixture gel, wherein the amount of the seeds added accounts for 0 to 5% of the mass of the mixture gel.

[0016] As a preferred embodiment of the present invention, the crystallization reaction in step (2) is stirred at a rotation speed of 50 rpm, the reaction temperature is controlled at 160° C., and the reaction time is 2 to 4 days.

[0017] As a preferred embodiment of the present invention, the drying temperature in step (2) is 80°C.

[0018] Description of the invention principle:

[0019] Compared with the more mature technology of using surfactants to assist in the synthesis of ultrathin MWW zeolite nanosheets, there is currently no report on the synthesis of ultrathin MWW zeolite nanosheets using a single small molecule template.

[0020] The traditional method uses the hydrophobic carbon chain of the surfactant to separate the MWW lamellae, but after calcination to remove the template agent and the surfactant, the lamellae are stacked to form thicker MWW zeolite nanosheets. The present invention innovatively proposes a new solution to solve the stacking problem by constructing a layer of curved hydrophobic carbon chains on the surface of the MWW lamellae. Due to the repulsion of the hydrophobic carbon chains, the MWW lamellae are naturally separated, and no treatment such as ultrasound is required, and the lamellae remain unstacked after calcination. Considering that there are a large number of Al sites in the 12-membered ring "pocket" on the surface of the MWW zeolite lamellae, N positive ions are required to balance its negative charge, and the monolayer MWW zeolite only has sinusoidal 10-membered ring channels, so the template agent needs to be flexible. Based on this, the present invention uses a double-headed quaternary ammonium salt template agent with certain flexibility to synthesize ultra-thin MWW zeolite nanosheets, thereby realizing the synthesis of ultra-thin MWW zeolite nanosheets with a single small molecule template agent.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The product prepared by the present invention not only maintains good crystallinity and purity, but also can achieve controllable thickness of MWW zeolite nanosheets by adjusting the silicon-aluminum ratio of the feed.

[0023] 2. The entire preparation process of the present invention does not use expensive surfactants for stripping or auxiliary synthesis, thus avoiding the disadvantages of sample amorphization, complex operation and high price caused by the post-treatment process.

[0024] 3. The product prepared by the present invention has a large specific surface area and a wide synthesis range of silicon-aluminum ratio, and the obtained product has potential application value for some important catalytic reactions. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the XRD spectrum of the MWW-C4 zeolite nanosheets prepared in Example 1.

[0026] Figure 2 This is a SEM image of the MWW-C4 zeolite nanosheets prepared in Example 1.

[0027] Figure 3 This is a TEM image of the MWW-C4 zeolite nanosheets prepared in Example 1.

[0028] Figure 4 This is the solid aluminum nuclear magnetic spectrum of the MWW-C4 zeolite nanosheets prepared in Example 1.

[0029] Figure 5 This is the XRD spectrum of the MWW-C5 zeolite nanosheets prepared in Example 4.

[0030] Figure 6This is the SEM image of the MWW-C5 zeolite nanosheets prepared in Example 4.

[0031] Figure 7 This is a TEM image of the MWW-C5 zeolite nanosheets prepared in Example 4. DETAILED DESCRIPTION

[0032] The implementation of the present invention will be described in detail below in conjunction with specific embodiments.

[0033] Example 1: MWW zeolite nanosheets (MWW-C4) were synthesized using N,N'-diethyl-N,N,N',N'-tetramethyl-1,4-diammonium hydroxide (EtMe2(CH2)4Me2Et) as a template.

[0034] 40wt.% silica sol, sodium aluminate, sodium hydroxide, EtMe2(CH2)4Me2Et solution and deionized water were added to a beaker and stirred overnight; 0% of the mass percentage of seeds was added to the mixture and stirred evenly to obtain a gel; the gel was transferred to a reactor and placed in a 160℃ oven for dynamic crystallization (stirring at 50rpm) for 2 days, and the sample obtained after filtration, washing and drying at 80℃ was named MWW-C4. The amount of each reaction raw material added should make the composition and molar ratio of the gel before loading into the reactor 1.0SiO2: 0.033Al2O3: 0.1Na2O: 0.6OSDA: 40H2O.

[0035] Figure 1 is the XRD spectrum of the sample. It can be seen from the figure that the product has a typical MWW zeolite molecular sieve structure.

[0036] Figure 2 Figure 2 is a scanning electron microscope (SEM) photo of the sample. From the SEM photo, we can see that the sample has a typical flake morphology. Figure 3 The transmission electron microscope (TEM) images of the samples at different magnifications show that the thickness of the nanosheet is about 2.5 nm. Figure 4 This is the solid aluminum NMR spectrum of the sample, which shows that the aluminum species in the sample are all four-coordinated aluminum on the framework.

[0037] Example 2: Synthesis of MWW zeolite nanosheets (MWW-C4) using N,N'-diethyl-N,N,N',N'-tetramethyl-1,4-diammonium hydroxide (EtMe2(CH2)4Me2Et) as a template

[0038] 40wt.% silica sol, sodium aluminate, sodium hydroxide, EtMe2(CH2)4Me2Et solution and deionized water were added to a beaker and stirred overnight; 2.5% of seed crystals were added to the mixture and stirred evenly to obtain a gel; the gel was transferred to a reactor and placed in a 160℃ oven for dynamic crystallization (stirring at 50rpm) for 3 days. The sample obtained after filtration, washing and drying at 80℃ was named MWW-C4. The amount of each reaction raw material added should make the composition and molar ratio of the gel before loading into the reactor 1.0SiO2: 0.016Al2O3: 0.05Na2O: 0.4OSDA: 60H2O.

[0039] Example 3: Synthesis of MWW zeolite nanosheets (MWW-C4) using N,N'-diethyl-N,N,N',N'-tetramethyl-1,4-diammonium hydroxide (EtMe2(CH2)4Me2Et) as a template

[0040] 40wt.% silica sol, sodium aluminate, sodium hydroxide, EtMe2(CH2)4Me2Et solution and deionized water were added to a beaker and stirred overnight; 5% of seed crystals were added to the mixture and stirred evenly to obtain a gel; the gel was transferred to a reactor and placed in a 160℃ oven for dynamic crystallization (stirring at 50rpm) for 4 days. The sample obtained after filtration, washing and drying at 80℃ was named MWW-C4. The amount of each reaction raw material added should make the composition and molar ratio of the gel before loading into the reactor 1.0SiO2: 0.056Al2O3: 0.15Na2O: 0.8OSDA: 80H2O.

[0041] Example 4: Synthesis of MWW zeolite nanosheets (MWW-C5) using N,N'-diethyl-N,N,N',N'-tetramethyl-1,5-pentanediammonium hydroxide (EtMe2(CH2)5Me2Et) as a template

[0042] 40wt.% silica sol, sodium aluminate, sodium hydroxide, EtMe2(CH2)5Me2Et solution and deionized water were added to a beaker and stirred overnight; 0% of seed crystals were added to the mixture and stirred evenly to obtain a gel; the gel was transferred to a reactor and placed in a 160℃ oven for dynamic crystallization (stirring at 50rpm) for 2 days. The sample obtained after filtration, washing and drying at 80℃ was named MWW-C5. The amount of each reaction raw material added should make the composition and molar ratio of the gel before loading into the reactor 1.0SiO2: 0.016Al2O3: 0.1Na2O: 0.6OSDA: 40H2O.

[0043] Figure 5is the XRD spectrum of the sample. It can be seen from the figure that the product has a typical MWW zeolite molecular sieve structure.

[0044] Figure 6 Figure 2 is a scanning electron microscope (SEM) photo of the sample. From the SEM photo, we can see that the sample has a typical flake morphology. Figure 7 Figure 1 is a transmission electron microscope (TEM) image of the sample. From the TEM image, we can see that the thickness of the nanosheet is about 5 nm.

[0045] Example 5: Synthesis of MWW zeolite nanosheets (MWW-C5) using N,N'-diethyl-N,N,N',N'-tetramethyl-1,5-pentanediammonium hydroxide (EtMe2(CH2)5Me2Et) as a template

[0046] 40wt.% silica sol, sodium aluminate, sodium hydroxide, EtMe2(CH2)5Me2Et solution and deionized water were added to a beaker and stirred overnight; 2.5% of seed crystals were added to the mixture and stirred evenly to obtain a gel; the gel was transferred to a reactor and placed in a 160℃ oven for dynamic crystallization (stirring at 50rpm) for 3 days. The sample obtained after filtration, washing and drying at 80℃ was named MWW-C5. The amount of each reaction raw material added should make the composition and molar ratio of the gel before loading into the reactor 1.0SiO2: 0.016Al2O3: 0.05Na2O: 0.4OSDA: 60H2O.

[0047] Example 6: Synthesis of MWW zeolite nanosheets (MWW-C5) using N,N'-diethyl-N,N,N',N'-tetramethyl-1,5-pentanediammonium hydroxide (EtMe2(CH2)5Me2Et) as a template

[0048] 40wt.% silica sol, sodium aluminate, sodium hydroxide, EtMe2(CH2)5Me2Et solution and deionized water were added to a beaker and stirred overnight; 0% of seed crystals were added to the mixture and stirred evenly to obtain a gel; the gel was transferred to a reactor and placed in a 160℃ oven for dynamic crystallization (stirring at 50rpm) for 4 days. The sample obtained after filtration, washing and drying at 80℃ was named MWW-C5. The amount of each reaction raw material added should make the composition and molar ratio of the gel before loading into the reactor 1.0SiO2: 0.056Al2O3: 0.15Na2O: 0.8OSDA: 80H2O.

[0049] The above are only several implementation cases of the present invention, and are not intended to limit the present invention in any form. Although the present invention has been disclosed as a preferred implementation case, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent implementation cases of equivalent changes using the above disclosed structure and technical content without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above implementation cases based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for synthesizing ultrathin MWW zeolite nanosheets using a small molecule template agent, characterized in that: The following steps are involved: (1) Add silica sol, sodium aluminate, sodium hydroxide, template and deionized water into a beaker and stir overnight to obtain a mixture gel; (2) transferring the mixed gel into a reactor and placing it in an oven for crystallization reaction; filtering, washing and drying the reaction product to obtain MWW zeolite nanosheets; In the above steps, the amount of each reaction raw material added is controlled so that the molar ratio of the components contained in the gel before being loaded into the reactor is converted to: 1.0 SiO2: 0.016-0.056 Al2O3: 0.05-0.15 Na2O: 0.4-0.8 template: 40-80 H2O; The template agent is N,N'-diethyl-N,N,N',N'-tetramethyl-1,4-butylene diammonium hydroxide or N,N'-diethyl-N,N,N',N'-tetramethyl-1,5-pentane diammonium hydroxide.

2. The method according to claim 1, characterized in that When a template is used in step (1), it is added in the form of an aqueous template solution and mixed.

3. The method according to claim 1, characterized in that The mass percentage of silica sol in step (1) is 40wt.%.

4. The method according to claim 1, characterized in that: Step (1) further comprises adding MWW zeolite seed crystals to the mixture gel, wherein the amount of the seed crystals added accounts for 0 to 5% of the mass of the mixture gel and is not zero.

5. The method according to claim 1, characterized in that During the crystallization reaction in step (2), the stirring speed is 50 rpm, the reaction temperature is controlled at 160° C., and the reaction time is 2 to 4 days.

6. The method according to claim 1, characterized in that The drying temperature in step (2) is 80°C.

Citation Information

Patent Citations

  • A method for the preparation of MWW type zeolite

    CN103384644A

  • A process for preparing a zeolitic composition having MWW-type framework

    IN201721002734A